The Role of Crisis Management in the Corona Pandemic and its Impact on Overcoming the Crisis: An Applied Study on AlFanar – Projects Company (The International Journal for Scientific Research, 2024)
The field study conducted delved into the attitudes of managers and employees at Al Fanar Projects Company towards crisis management, gauging their interest and interaction through various questions related to awareness levels and the application of crisis management strategies, particularly during the COVID-19 pandemic. The study revealed a positive and effective role of crisis management in achieving the desired goal of transitioning the company and its operations to safety during the pandemic, enabling it to overcome the crisis effectively.At the outset, the study reviewed previous specialized research on crisis management, comparing the findings with those derived from our study. The results of the comparisons indicated that implementing crisis management strategies in companies plays a crucial role in protecting them from expected and unexpected risks through pre-planning and developing crisis management strategies before their occurrence. The success and excellence of companies are linked to the company's ability to manage its internal and external crises alike.The study then outlined the main objectives, including identifying the role of crisis management in dealing with the necessary procedures to overcome the COVID-19 pandemic, assessing the plans and crisis management strategies adopted by Al Fanar Company, and measuring the effectiveness of these measures, which focused on internal and external procedures.Furthermore, the study clarified some theories related to crisis management and introduced procedural definitions related to management and crises. Finally, the study concluded with a presentation and discussion of the research results, analyzing the demographic data of a sample of Al Fanar Projects Company employees, along with analyzing the sample's responses to the research tool (questionnaire). The questions were analyzed and answered in detail, followed by hypothesis testing to reach the conclusion.In conclusion, the researchers presented some recommendations aimed at developing and improving the concept of crisis management in companies.
Keywords: Crisis Management; Corona Pandemic; Covid19